Why Foreign Direct Investment Has Not Promoted Social Housing Development in Vietnam - Phuong, T. Thai-; Phuong, N. Pham-; Son, L. Nguyen- (International Journal of Accounting and Economics Studies, 2025)
This study investigates the misalignment between Foreign Direct Investment (FDI) and social housing development ‎‎(SHD) in Vietnam, focusing on six major urban centers: Hanoi, Hai Phong, Da Nang, Binh Duong, Ho Chi Minh City, ‎and Can Tho, over the period 2010–2022. The research direction seeks to understand why FDI, despite its pivotal ‎role in driving economic growth, has not effectively supported social housing projects, which are critical for address-‎ing housing needs of low-income groups amid rapid urbanization. The primary objective is to identify the structural ‎and contextual factors hindering FDI’s contribution to SHD, while proposing policy reforms to align FDI with sus-‎tainable and inclusive urban development goals. A mixed-methods approach is employed, integrating quantitative ‎analyses (including normality tests, Pearson correlation, and linear regression) with qualitative insights derived from ‎prior studies, to provide a comprehensive examination of the FDI-SHD relationship. The study aims to elucidate the ‎key factors driving this misalignment, assess regional policy variations across major cities, and offer actionable poli-‎cy recommendations, such as reforming tax incentives, promoting public-private partnership models, and streamlin-‎ing administrative processes, to enhance FDI’s role in social housing development, contributing to sustainable urban ‎frameworks in Vietnam and offering lessons for other developing economies.
Keywords: Economic Disconnect; Foreign Direct Investment (FDI); Policy Recommendations; Social Housing Development; ‎Urban Policy